2015
DOI: 10.1371/journal.pone.0116097
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Marker Protein Expression Is an Indicator of Olfactory Receptor-Associated Events in Non-Olfactory Tissues

Abstract: Olfactory receptor (OR)-associated events are mediated by well-conserved components in the olfactory epithelium, including olfactory G-protein (Golf), adenylate cyclase III (ACIII), and olfactory marker protein (OMP). The expression of ORs has recently been observed in non-olfactory tissues where they are involved in monitoring extracellular chemical cues. The large number of OR genes and their sequence similarities illustrate the need to find an effective and simple way to detect non-olfactory OR-associated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 66 publications
2
71
0
Order By: Relevance
“…Thus, by tuning noise and response kinetics, OMP is a key regulator of ORN physiology. It will be interesting to investigate whether OMP might also play a similar role in other tissues, given its recently reported broader expression pattern (Kang et al, 2015).…”
Section: From Single-cell Physiology To Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, by tuning noise and response kinetics, OMP is a key regulator of ORN physiology. It will be interesting to investigate whether OMP might also play a similar role in other tissues, given its recently reported broader expression pattern (Kang et al, 2015).…”
Section: From Single-cell Physiology To Behaviormentioning
confidence: 99%
“…Olfactory marker protein (OMP), a protein thought to be exclusively expressed in mature ORNs (Margolis, 1972), has been shown to be involved in olfactory kinetics. Interestingly, OMP was recently found to be expressed in other nonolfactory tissues, often with ORs and AC3 (Kang et al, 2015). Electro-olfactograms from OMP knock-out (KO) mice have slower onset and decay kinetics compared with wild type (WT; Buiakova et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, some dead newborn Smo fl/fl pups had milk in the stomach, indicating that the mortality was not necessarily due to inability to suckle. An alternative possibility was that the neonatal mortality was dependent on a lack of Smo signaling in OMP-positive cells other than OSNs, e.g., vomeronasal sensory neurons or OMP-positive nonolfactory cells (18,19). Because of the neonatal mortality, we analyzed mice at embryonic day 18.5 (E18.5).…”
Section: Significancementioning
confidence: 99%
“…Recent studies have reported that OMP and ORs are expressed in non-olfactory tissues, including the pancreas, colon, bladder, and thyroid gland 15,18,[28][29][30] . However, there have been no previous investigations on the expression and physiological functions of OMP in the pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not known whether OMP function is conserved across tissues. Recent studies have suggested a link between OMP and the endocrine system, especially in neuroendocrine neoplasia and hormone secretion [15][16][17][18] . However, to date, there have been no studies investigating the role of OMP in the functioning of the pituitary gland, which is considered the master regulator of the neuroendocrine system.…”
Section: Introductionmentioning
confidence: 99%